1992
DOI: 10.3354/meps087215
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns of juvenile penaeid prawns in response to artificial tidal and day-night cycles: a comparison of three species

Abstract: Activity patterns of Penaeus merguiensjs, P. esculentus and Metapenaeus endeavouri were studied in response to simulated tidal and day-night cycles in the laboratory. When these cycles were imposed separately, each species was more active at night and near the times of high tide. However, when the tidal and day-night cycles were imposed together, the relative strengths of the responses to the 2 factors differed among species. M. endeavouri was strongly influenced by the day-night cycle; virtually no activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Evidence of diel movements has also been found for some species through observations of a behavioural response to light in laboratory conditions (e.g. Vance, 1992;Borg et al, 1997). Telemetric studies have also shown that many fish move cyclically between the day and night sections of a home range.…”
Section: Diel Movementsmentioning
confidence: 86%
See 1 more Smart Citation
“…Evidence of diel movements has also been found for some species through observations of a behavioural response to light in laboratory conditions (e.g. Vance, 1992;Borg et al, 1997). Telemetric studies have also shown that many fish move cyclically between the day and night sections of a home range.…”
Section: Diel Movementsmentioning
confidence: 86%
“…In contrast, Zeller (1997) reported high site fidelity throughout day and night for rockcod (Plectropomus leopardus) in the Great Barrier Reef, Australia. A diel cycle of emergence and movement is also common in burrowing decapod crustaceans (Vance and Staples, 1992), with most species burrowing during the day and emerging at night (Vance, 1992). Some species of penaeid prawns show peaks in activity following a 'bimodal crepuscular pattern', with a peak after dusk and before dawn (Dall et al 1990).…”
Section: Diel Movementsmentioning
confidence: 99%
“…In addition to seasonal changes, there is a diel variability related to short-term movements of the animals during the day-night cycle along the seagrass shoots or from adjacent habitats. There is some information on the diel variation in seagrass beds regarding organisms with high mobility such as fish (Gray et al 1998;Griffiths 2001;Petrakis et al 2001;Guest et al 2003) and crustaceans (Vance 1992;Vance et al 1994;Guest et al 2003;García-Raso et al 2006), but relevant information on molluscan taxocoenoses is scarce (Templado 1982;Le Loeuff and Intès 1999;Mattila et al 1999;Sánchez-Jerez et al 1999;.…”
Section: Introductionmentioning
confidence: 99%
“…In general, P. muelleri follows the pattern proposed by Dall et al (1990) for penaeids, i.e., most marine shrimp species remain burrowed during the day and emerge at night. Diurnal burrowing activity is common in the majority of penaeids (STONER, 1991;VANCE, 1992;BISHOP et al, 2008;SIMÕES et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Dall et al (1990) suggested that most penaeid shrimp remain burrowed in the substratum during the day and emerge at night. This behavior provides protection against predators and also allows for a lower energy expenditure because the shrimp decrease their metabolic rate when burrowed (LAKSHMI et al, 1976;VANCE, 1992;CLARK et al, 2003). Laboratory experiments have indicated that at least certain species of Penaeidae are much more active at night and are thus more vulnerable to capture by nets (PONTES; ARRUDA, 2005;PONTES, 2006).…”
Section: Introductionmentioning
confidence: 99%